Prudent Principle Dalam Penyaluran Kredit Pada Layanan Digital Perbankan - Sopamena, Siska Vilonia Indah; Tjoanda, Merry; Kuahaty, Sarah Selfina (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
In credit distribution carried out through digital banking services, approval of credit applications and data verification are processed more quickly than if done conventionally. This gives rise to the implication that the prudent principle for providing credit or other financing has not been fully implemented and could result in losses for the bank and the Debtor Customer if it continues if the prudent principle is not implemented properly. The aim of this research is to review and discuss the application of the Prudent Principle in the procedure of acquiring credit through digital banking services as well as whether the digital procedure to acquire credit could provide protection for the parties. The legal research method used for this research is based on primary, secondary, and tertiary legal materials, and uses a statutory approach and a conceptual approach. The results of the research show that the prudent principle must be implemented effectively to determine whether the prospective Debtor Customer can be trusted and is able to make payments so that both parties do not experience losses. How quickly the approval of credit applications made through digital banking services shows that the implementation of prudent principles has not been implemented properly when compared to credit applications made conventionally. Legal protection for the parties involved can be implemented by using relevant laws and regulations as a form of preventive legal protection. There is also repressive legal protection in the form of alternative dispute resolution or through civil lawsuits in court.